A microfluidic chip and its use in characterising the particle-scale behaviour of microbial-induced calcium carbonate precipitation (MICP). Issue 12 (28th January 2019) - Wang, Yuze; Soga, Kenichi; Dejong, Jason T.; Kabla, Alexandre J.
Abstract : Microbial-induced calcium carbonate precipitation (MICP) is an innovative ground improvement technique which can enhance the strength and stiffness of soils and can also control their hydraulic conductivity. These engineering properties of MICP-treated soils are affected by the particle-scale behaviour of the precipitated calcium carbonate – namely, the composition, amount and distribution, which are controlled by the MICP process occurring at the particle scale. In this study, a microfluidic chip was designed and fabricated to improve understanding of MICP at the particle scale by observing the behaviour of bacteria and calcium carbonate crystals during this process. It was found that bacteria became evenly distributed throughout the microfluidic chip after the injection of bacterial suspension, grew during bacterial settling and detached during the injection of cementation solution. Bacteria aggregated during the cementation solution injection, and calcium carbonate crystals formed at narrow pore throats or open pore bodies either during or after the cementation solution injections.